Evolution of Acetic Acid Bacteria During Fermentation and Storage of Wine - Joyeux, A. (1984)
Acetic acid bacteria were present at all stages of wine making, from the mature grape through vinification to conservation. A succession of Gluconobacter oxydans, Acetobacter pasteurianus, and Acetobacter aceti during the course of these stages was noted. Low levels of A. aceti remained in the wine; they exhibited rapid proliferation on short exposure of the wine to air and caused significant increases in the concentration of acetic acid. Higher temperature of wine storage and higher wine pH favored the development and metabolism of these species.